Tafsir Education and Its Challenges in Relation to Halaqat Al-'Ilmiyyah in Borno State, Nigeria - Ali, Muhammad Bukar; Audu, Fatima Muhammad; Habib, Jibrin Mohammed (QiST: Journal of Quran and Tafseer Studies, 2025)
This research examines the major challenges confronting tafsir education in halaqat al-'ilmiyyah (study circles) within Borno State, Nigeria. The objectives of the research are to assess the current state of tafsir teaching, identify the main obstacles affecting its effectiveness, analyze their implications on Islamic educational goals, particularly in preserving religion (ḥifẓ al-dīn) and intellect (ḥifẓ al-'aql) as emphasized in Maqasid al-Shari'ah, and to propose strategies for improving the system. The research employed a mixed-methods approach, combining eighty (80) questionnaires administered to students of halaqat and twenty (20) semi-structured interviews with scholars actively engaged in tafsir teaching. Findings reveal that the absence of a structured curriculum, linguistic barriers, socio-economic hardship, insecurity, and resistance to modern educational innovations significantly hinder effective tafsir education. The lack of standardization in teaching content and limited access to materials reduce learning consistency and depth. Insecurity, especially the Boko Haram insurgency, further disrupts the continuity of study circles across affected areas. The research recommends the establishment of a unified curriculum, teacher training, improved resource support, and collaboration with educational authorities to enhance the quality and sustainability of tafsir learning in the region.